The what to eat when cookbook : 135+ deliciously timed recipes - Roizen, Michael F.; Crupain, Michael; Perko, Jim; Spiker, Ted (National Geographic, 2020)
"A cookbook that puts into effect a strategic eating plan developed by the authors to help promote healthier living, disease prevention, better performance and a longer life"--